Teachers Use of Questioning in the ESL Classroom: Questioning as a Teaching Strategy - Husniah, Sahamid; Nor Ashikin, Abdul Aziz; Nor, Syaheeda (Global Academic Institute, 2016)
The employment of questioning as an instructional tool has always been considered part of the teaching tradition, and has a long history. The focus on teacher questioning recently has been due to the opportunities that teacher questioning can provide for students to become actively engaged while also developing thinking skills. This paper describes an ongoing study of three teachers’ classroom questioning behavior in an ESL proficiency course in a public university in Malaysia. The study aims to investigate the types of questions teachers ask in class and the responses elicited from students. The study is conducted on a small scale and is in-depth in nature, using three instruments for triangulation to help to validate the findings. Data is collected using a questionnaire, a semi-structured interview protocol to determine teacher rationale for teacher questions used in the classroom, and video-taped classroom interactions between teacher and students. This paper presents the preliminary findings of the study based on data collected from the video recordings of the class sessions. This paper also recommends strategies to promote teacher questioning and student learning based on the preliminary findings